The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.6000/1929-6037.2012.01.02.7
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Fouling Potential of Secondary Effluent Organic Matter (EfOM) from Conventional Activated Sludge Process

Abstract: Secondary effluent organic matter (EfOM) from a conventional activated sludge process was filtered through constant-pressure dead-end filtration tests with a sequential ultrafiltration (UF, molecular weight cut-off (MWCO) of 10k Dalton) and nanofiltration (NF, MWCO of 200 Dalton) array to investigate its membrane fouling potential. Advanced analytical methods including liquid chromatography with online carbon detection (LC-OCD) and fluorescent excitation-emission matrix (F-EEM) were employed for EfOM character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…HS is hydrophobic-DOC fraction of seawater. These compounds are mainly removed due to the potential electrostatic interaction [34]. Thus, it could not be removed by hydrophilic UF membrane.…”
Section: Mfi-uf and Ks Vs Aocmentioning
confidence: 99%
“…HS is hydrophobic-DOC fraction of seawater. These compounds are mainly removed due to the potential electrostatic interaction [34]. Thus, it could not be removed by hydrophilic UF membrane.…”
Section: Mfi-uf and Ks Vs Aocmentioning
confidence: 99%
“…Therefore, the four fouling mechanisms in the UF process of the surface water could occur simultaneously in theory. Wei and Amy [ 26 ] found the simultaneous occurrence of two fouling mechanisms during the UF process of the wastewater treatment plant effluent. Corbaton et al [ 27 ] found that single models did not characterize the membrane fouling mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…Each of these components or fractions will contribute differently to membrane fouling due to individual properties, for example, hydrophobicity and charge . The success of the fractionated methodology decreases with the number of separated fractions.…”
Section: Introductionmentioning
confidence: 99%
“…Each of these components or fractions will contribute differently to membrane fouling due to individual properties, for example, hydrophobicity and charge. 19 The success of the fractionated methodology decreases with the number of separated fractions. In addition, a major problem with these techniques occurs when organic matter compounds irreversibly adsorb onto the resin and consequently these fractions cannot be recovered.…”
Section: Introductionmentioning
confidence: 99%